Neotectônica no Amazonas: análise geomorfológica-geológica na BR 174 - Deivison Carvalho Molinari; Daniella Paiva de Carvalho (Confins)
The objective of the present work was to perform geomorphological analysis of the region of kilometer 99 on the BR-174 federal highway, where there is exposure of packages of marine coal leaflets of the Urubu River basin, and especially the morphometric elements of the economic category, and the geological aspects, such as: lineaments and geological formation. These gray leaflets are built into the package, recorded in the presence of bioturbated fossils, originated from the activities of organisms used for transgressions and marine regressions of glacial influence. The Urubu River is not on the edge of the municipality of Presidente Figueiredo and not in the Trombetas Group, composed by the following forms: Nhamundá (oldest), Pitinga (intermediate) and Manacapuru (younger), being the latter formation the most representative of the class. of use of the rock model in this outcrop. This river has a unique feature of NE-SW direction, which is indicative of a lineage river with origin of structural control of the Black and Solimons Rivers region.